Xylosandrus germanus in Central Europe: Spread into and within the Czech Republic. (5th May 2020) - Fiala, Tomáš; Holuša, Jaroslav; Procházka, Jiří; Čížek, Lukáš; Dzurenko, Marek; Foit, Jiří; Galko, Juraj; Kašák, Josef; Kulfan, Jan; Lakatos, Ferenc; Nakládal, Oto; Schlaghamerský, Jiří; et al.
Abstract: Invasive organisms represent great threats to ecosystems and great challenges to forest management. In Europe, the black timber bark beetle ( Xylosandrus germanus ) is an invasive secondary pest that mostly attacks the logs of felled trees. We showed the invasion history for Europe and using many local surveys, we summarize the current distribution and other available information on X. germanus in the Czech Republic. We report that this species is distributed from the lowlands to the mountains in the Czech Republic; it is widespread in the eastern half of the country, where it is more abundant in the warmer south and southeast areas than in the cooler areas. Most (78%) of the known localities are at elevation below 400 m a.s.l. Although an ice storm greatly increased X. germanus abundance near the border with Austria, its high abundance did not result in damage to standing trees. Presence of X. germanus in the Czech Republic for over 10 years has not led to heavy tree infestation.